2014
DOI: 10.1021/ja501591n
|View full text |Cite
|
Sign up to set email alerts
|

Complete Colloidal Synthesis of Cu2SnSe3 Nanocrystals with Crystal Phase and Shape Control

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 60 publications
5
97
0
Order By: Relevance
“…The final Cu 0.66 Sn 0.33 Se NCs exhibited a main peak at 179 cm –1 and three minor peaks at 205, 228, and 245 cm –1 , in good agreement with literature data for the Cu 2 SnSe 3 phase. 37,38 The appearance and the progressive shift of the Cu 0.66 Sn 0.33 Se Raman modes that followed the entrance of Sn 4+ ions inside the Cu 2- x Se NCs support the formation of solid Cu 2–4 y Sn y Se solutions as intermediate phases.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The final Cu 0.66 Sn 0.33 Se NCs exhibited a main peak at 179 cm –1 and three minor peaks at 205, 228, and 245 cm –1 , in good agreement with literature data for the Cu 2 SnSe 3 phase. 37,38 The appearance and the progressive shift of the Cu 0.66 Sn 0.33 Se Raman modes that followed the entrance of Sn 4+ ions inside the Cu 2- x Se NCs support the formation of solid Cu 2–4 y Sn y Se solutions as intermediate phases.…”
Section: Resultsmentioning
confidence: 88%
“…This is most likely due to the very low Raman scattering efficiency of this phase, as already observed recently by Izquierdo-Roca et al 36 Starting from the pristine Cu 2- x Se NCs, already at the very early stages of the Cu + → Sn 4+ exchange (for example when the composition was Cu 1.85 Sn 0.07 Se, as measured by elemental analysis via ICP) a broad peak at about 185 cm –1 was observed (see Figure 1c). This peak appears to be related to the main mode of the Cu 0.66 Sn 0.33 Se phase, 37,38 albeit blue-shifted by few cm –1 from that mode. Upon increasing the amount of Sn 4+ ions incorporated in the Cu 2- x Se NCs (for example at a composition corresponding to Cu 1.20 Sn 0.19 Se), all peaks traceable to the Raman modes of the Cu 2 SnSe 3 phase were observed, although almost all of them were slightly blue-shifted from those modes.…”
Section: Resultsmentioning
confidence: 89%
“…Ternary copper tin chalcogenides (CTAs; A=S, Se, Te) have a large variety of stable phases, among which Cu 2 SnA 3 is the most studied. Several reports show that the capping ligands present in the reaction mixture have a crucial impact on the crystal structure of the resulting CTS or CTSe NCs . For example, cubic and wurtzite crystal structures have been reported by Ryan and co‐workers upon using elemental selenium at elevated temperatures and diphenyl diselenide, respectively (Figure ) .…”
Section: Ternary Copper Chalcogenidesmentioning
confidence: 99%
“…3 During the synthesis of multicomponent copper chalcogenides, we have observed that the temperature range for the growth of WZ phase is 220−280°C and for ZB growth is 255−310°C. 37 If the nucleation temperature is higher (>280°C) than the growth temperature then the resulting nanocrystals tend to have the 3-D morphology with a tetrahedrally coordinated ZB core and WZ derived arms. Contrary to this, when the nucleation is achieved at a much lower temperature (<220°C) with the growth at higher temperatures, 1-D linear structures are formed having a WZ core and two ZB-derived tips on either end.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…Wang et al discovered that the use of copper chloride (Cu(I)Cl) (highly reactive Cu source) along with tin chloride as metal precursors provided optimal control over separation of nucleation and growth events to form polytypic Cu 2 SnSe 3 tetrapod and linear heterostructures. 37 Coughlan et al for CZTS polytypic nanocrystals reported that the combination of metal chlorides as precursors along with OLA prompts the growth of biphasic heterostructures. 38 We have observed lately that by separating out the role of precursor and ligand species, it is possible to tune the shape and phases of complex polytypic structures.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%